Gaskets design, selection, and testing - Czernik, Daniel E. (McGraw-Hill, 1996)
Don't Blow A Gasket. . . Pick up Daniel E. Czernik's Gasket Handbook instead and arm yourself with all the know-how you need to design dependable, environment-friendly, long-lasting, high-performance gaskets. It's the only guide to cover design, selection, performance, efficiency, reliability, and testing of every type of ``static'' seal gasket: chemical, o-ring, metallic, and non-metallic. You'll find all the latest ASME codes, the proposed new ASME gasket constants, and in-depth explanations of: initial seal creation; seal maintenance; stress distribution testing; gasket design and environmental conditions; gasket installation; joint and gasket design and selection; sealing enhancements; rubber gaskets; failure mode and effects analysis; o-ring seals; finite element analysis; computers and gaskets; chemical gaskets; and more.